Numerical Modelling of NACA 0015 Airfoil Under the Erosion Condition - Rayhan Fariansyah Billad; James Julian; Fitri Wahyuni; Waridho Iskandar; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
Airfoil that experiences erosion caused by flying debris that hit the airfoil can affect the performance of the airfoil. This research was studied to determine the effect of erosion with varying erosion length using numerical methods on the performance of the NACA 0015 airfoil. This research was simulated using the Computational Fluid Dynamics (CFD) approach. Reynolds Averaged Navier-Stokes (RANS) is implemented as the governing equation. The turbulence model used in this research is the k-epsilon model. The Reynolds number used is 1.5 x 10⁶. This research proves that the erosion effect can reduce the Cl value and increase the Cd value on the NACA 0015 airfoil. Increasing the erosion length on the airfoil can also affect the Cl value and Cd value, but this effect is insignificant. In the contour visualization, it can be seen that the airfoil that is experiencing erosion has a pressure contour that increases in the upper chamber and decreases in the lower chamber compared to the airfoil that does not experience erosion so that it can reduce the lifting force of the NACA 0015 airfoil. The flow velocity and streamline contours also show greater circulation in the erosion airfoil, which can accelerate the stall by 1o AoA. Then, variations in increasing erosion length on the airfoil do not show any significant differences in pressure contours or circulating flow.